2017
DOI: 10.1021/acs.est.6b03107
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Modern Stormwater Management Practices on Transport of Road Salt to Surface Waters

Abstract: Application of road salts in regions with colder climates is leading to ground and surface water contamination. However, we know little about how modern stormwater management practices affect the movement of road salt through urban watersheds. We investigated groundwater contamination and transport of road salts at two stormwater ponds in Baltimore County, Maryland. In association with the ponds, we documented a plume of contaminated groundwater that resulted in Cl loadings to the adjacent stream of 6574 to 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 35 publications
6
69
0
Order By: Relevance
“…Roseen et al [50] found that frost penetration had a negligible impact on most BMPs performance; Snodgrass et al [53] conclude that green infrastructure BMPs cannot treat road salts and instead advocate for source controls.…”
Section: Design Advice From Interviews (I) and Authors (A) For In-strmentioning
confidence: 99%
“…Roseen et al [50] found that frost penetration had a negligible impact on most BMPs performance; Snodgrass et al [53] conclude that green infrastructure BMPs cannot treat road salts and instead advocate for source controls.…”
Section: Design Advice From Interviews (I) and Authors (A) For In-strmentioning
confidence: 99%
“…Hence, it is possible that chlorination rates can be influenced by changing pore water Clconcentrations and ionic strength such as during dry or wet periods and in areas with anthropogenic Cladditions to the soil, e.g. from road salt 37,38,39 .…”
Section: Effects Of Chloride Additionmentioning
confidence: 99%
“…For example found that while denitrification rates were higher in watersheds with LID practices (constructed stormwater wetlands and restored riparian areas), methane (CH4) emissions were also higher than in non-LID watersheds. Elevated chloride and conductivity were detected in stream baseflow and surface runoff downstream of stormwater infiltration basins, likely due to chloride enriched groundwater plumes originating from these stormwater controls (Snodgrass et al, 2017). Another useful tool was developed by Warsta et al (2017) to automate watershed delineation and characterization as part of building SWMM models.…”
Section: Watershed-scale Lid Assessmentmentioning
confidence: 99%